Nigeria's Polio Elimination Playbook: Lessons To Strengthening Health Systems For Other Eradicable Diseases - Fortune Effiong; Ikechukwu Peter Akanno; Udochukwu Godswill Anosike; Ayomide Timilehin Kayode; Atai Bassay Okon; Godsgift Chinemelum Iwendi; Gabriel Ilerioluwa Oke; Maureen Amuche Nwobodo; Leonard Ighodalo Uzairue (University of New South Wales, 2021)
According to the World Health Organization (WHO), poliomyelitis (polio) is a highly infectious viral disease that largely affects children under 5 years of age. In August 2020, Nigeria was declared free of the wild poliovirus by the WHO and United Nations International Children's Emergency Fund (UNICEF). This review assesses the available evidence on issues with Nigeria's efforts and challenges towards the fight against poliomyelitis such as the wild poliovirus (WPV) and vaccine-derived poliovirus (VDPV). Published grey literature was assessed to make this mini-review. No restriction on publication dates was applied during the literature search. Available data showed efforts such as strong government accountability framework; introduction of geographic information systems to ensure more efficient utilization of resources and coverage; the digitalization of vaccine delivery; optimal utilization of disease notification officers (DNOs) at every unit of the local government; commitment of resources from the federal government to states that were prone to the reoccurrence of Polio; improved social mobilization, supervision, and monitoring; as well as assistance from international organizations were deplored. Some of the notable challenges faced with the eradication of polio include the refusal of parents to consent to vaccinations for their children, reoccurrences due to poor supplies of potable water, religious bias from the northern region, differential routines, and supplemental immunization coverage. The lessons learned in polio eradication can be channeled into the elimination of other diseases, but efforts must be in place to continue to monitor the reoccurrence of polio and other emerging diseases through surveillance systems.